Critical success factors of interactive logbook application for industrial training in the plantation sector / Nur Qursyna Boll Kassim, Nur Suraya Abdullah and Nur Masriyah Hamzah - Boll Kassim, Nur Qursyna; Abdullah, Nur Suraya; Hamzah, Nur Masriyah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
This study examine the critical success factors of interactive logbook applications for industrial training in the plantation sector. The questionnaires were designed and distributed to the 200 respondents in the Faculty of Plantation and Agrotechnology, Universiti Teknologi MARA that undergone industrial training in various plantation sectors. The descriptive results showed that 86% of the students prefer to have an interactive logbook for their industrial training with 97.5% of them found that the interactive logbook is very interesting. The simple features of the interactive logbook recorded the highest percentage (70.4%) and were shown to be the most important success factors of the interactive logbook, followed by attractiveness (64.3%), informative (63.3%), and motivational and inspirational (37.2%). The usefulness of the interactive logbook has a score of 4 (98 respondents) to 5 (81 respondents).